2019
DOI: 10.1002/cam4.2239
|View full text |Cite
|
Sign up to set email alerts
|

Patterns and predictors of self‐reported clinical diagnosis and treatment for depression in prostate cancer survivors

Abstract: Background Appropriate depression care is a cancer‐care priority. However, many cancer survivors live with undiagnosed and untreated depression. Prostate cancer survivors may be particularly vulnerable, but little is known about their access to depression care. The goal of this study was to describe patterns and predictors of clinical diagnosis and treatment of depression in prostate cancer survivors. Methods Generalized estimating equations were used to evaluate indica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 78 publications
(152 reference statements)
0
6
0
1
Order By: Relevance
“…Fervaha et al [ 4 ] reported that risk factors for depression in PCa patients can be classified as both biological (e.g., advanced stage, greater burden of physical symptoms, and older age) and psycho-social (e.g., helplessness, low family support, not being partnered, and a personal history of psychiatric illness). Similarly, Erim et al [ 5 ] found that the most predictive factors for depression were ethnicity (i.e., not being Caucasian), unemployment, low annual income, past depression, comorbidities, treatment decisional regret, and nonadherence to exercise recommendations. Regarding suicidal ideation, Recklitis et al [ 6 ] found that it was significantly associated with employment status, poor physical and emotional functioning, greater symptom burden, higher frequency of significant pain, and depression.…”
Section: Introductionmentioning
confidence: 99%
“…Fervaha et al [ 4 ] reported that risk factors for depression in PCa patients can be classified as both biological (e.g., advanced stage, greater burden of physical symptoms, and older age) and psycho-social (e.g., helplessness, low family support, not being partnered, and a personal history of psychiatric illness). Similarly, Erim et al [ 5 ] found that the most predictive factors for depression were ethnicity (i.e., not being Caucasian), unemployment, low annual income, past depression, comorbidities, treatment decisional regret, and nonadherence to exercise recommendations. Regarding suicidal ideation, Recklitis et al [ 6 ] found that it was significantly associated with employment status, poor physical and emotional functioning, greater symptom burden, higher frequency of significant pain, and depression.…”
Section: Introductionmentioning
confidence: 99%
“…This may be inpatient (1.4%) or outpatient (2 in 3 cases). 7,8,28 Treatment options include antidepressants (eg, Prozac), psychotherapy (eg, cognitive behavioral therapy), or both (ie, combination therapy). Depression treatment promotes remission (from the second month of treatment) and prevents relapse or recurrence.…”
Section: Depression Treatmentmentioning
confidence: 99%
“…1,2 US patients with prostate cancer experience barriers when in need of depression care-for example, from a reluctance to seek mental healthcare, low depression screening rates in primary care clinics (4%), moderate accuracy of unassisted clinical diagnosis of depression (50%), and prospectively declining odds of clinical diagnosis and treatment of depression. [3][4][5][6][7][8] Fulfilling unmet depression care needs is a survivorship priority, 9 and a promising strategy for managing comorbid depression in US patients with prostate cancer is an integrated collaborative care model called the Depression Care for People with Cancer program (DCPC). [10][11][12] DCPC is an intensive, manualized, collaborative care-based multicomponent depression care model that is specifically designed to be integrated with cancer treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Health departments and cancer commissions in the US and the UK have all called for more attention to be paid to the depression in cancer patients (4). However, because of the lack of awareness among medical personnel and family caregivers, distress in cancer patients is frequently overlooked and under-treated (8). Furthermore, there are few effective pharmacotherapies (9,10).…”
Section: Introductionmentioning
confidence: 99%